Hand movement recognition for disabled person - Otthaman @ Othman, Firzana Haziera (2017)
Disabled person always having difficulty in communicate with other people. For example, deaf persons cannot hear well and struggle to speak correctly. They communicate with other people using sign language which is one way to communicate using combining hand shapes, orientation and movement of the hands. Therefore, the purpose of this project is to develop a hand movement recognition system using android based platform. The hand movement is detected using a glove sensor which is constructed using a set of bend sensors that will measure the value of hand movement of each five fingers. The main part of this project is the controller which is using Arduino microcontroller that will process data of the hand movement. Besides, an android application is developed to display related output and produce audio of the translated hand movement data. A set of data collection is analyzed to evaluate the accuracy of the hand movement recognition method. Overall, this project offers an alternation to learn the basic of sign language among disabled person in a low cost and efficient manner.